Risk prediction for subclinical carotid atherosclerosis in rotational shift workers in the arctic. (25th November 2020) - Shurkevich, N; Vetoshkin, A; Gapon, L; Simonyan, A; Kuznetsov, V
Abstract: Introduction: High prevalence of cardiovascular events at northern latitudes determines the necessity of studying mechanisms of formation and early diagnosis of atherosclerotic process. Purpose: To determine the most unfavorable prognostic factors that provide the percentage of correct prediction and high accuracy in detection of atherosclerotic plaque (ASP) in common carotid arteries (CCA) in rotational shift workers in the Arctic. Methods: Within 2010–2012 a study of 424 males aged 30–59 years at the medical unit "Gazprom dobycha Yamburg" (Yamburg settlement, 68°N) was performed. Patients were randomized into 2 groups according to blood pressure (BP). Gr.I included 294 people with BP more than 140/90 mmHg, arterial hypertension (AH) of 1, 2 stage and Gr.II included 130 people with BP less than 140/90 mmHg. Groups did not differ in age (46.9±5.8 years, p=0.435); total work experience in the Arctic: 16.5±6.8 years (p=0.512) and rotational shiftwork duration: 12.5±4.6 years (p=0.597). Office BP was 149.4±13.3/97.1±7.3 mmHg in Gr.I and 123.4±7.5/80.5±5.5 mmHg in Gr.II. Ultrasound examination of carotid arteries with determination of presence or absence of ASP in CCA and estimation of stenosis using NASCET method were performed; ambulatory blood pressure monitoring was conducted; blood glucose levels, total cholesterol, high-density lipoprotein cholesterol, low density lipoprotein cholesterol were determined. Statistical analysis was carried out using R (v. 3.6.1) programming language for statistical data processing of R Studio application package (v. 1.2.1335). Results: Signs of CCA atherosclerosis were revealed in 56% of patients with AH and in 25% of those without AH. According to multivariate analysis, three variables with the most significant set of predictors, associated with ASP in CCA with the percentage of correct prediction of 75.9% were selected by step-by-step method: diastolic BP24 (<0.0001), glucose (0.0167) and cholesterol (0.0439). Based on the obtained model, it was concluded that 1 mmHg increase in diastolic BP24 increases the risk for developing ASP by 5.9%, Exp. (Beta) = 1.059, 1 mmol/l increase in glucose and cholesterol escalates the risk by 44.1% and 25.2%, respectively: Exp. (Beta) = 1.441 and Exp. (Beta) = 1.252. Conclusion: The data obtained will improve accuracy for the early diagnosis of subclinical atherosclerosis of CCA, allow to prescribe lipid-lowering therapy timely and reduce the risk of adverse cardiovascular events in rotational shift workers in the Arctic. Funding Acknowledgement: Type of funding source: None